Analisis Pemungutan Pajak Air Permukaan Dalam Rangka Meningkatkan Pendapatan Asli Daerah Pada Bapenda Cikokol Tahun 2019-2021 - Wulan Saputri Listiani; Jiwa Pribadi Agustianto; Raden Kusyeni (Jurnal Ilmu Administrasi Publik, 2022)
The purpose of this study was to analyze of surface water tax collection in order to increase Regional Original Income (Pendapatan Asli Daerah - PAD), analyze the obstacles faced in implementing the surface water tax collection in to PAD, and analyze solutions in overcoming obstacles to the implementation of surface water tax collection in order to increase PAD in Tangerang Regional Revenue Agency 2019-2021. This study used a qualitative methodology. The researcher used primary and secondary data to investigate the specified problem. The data were collected through the interview method, literature/library method, and observation. This study used a descriptive method of data analysis, i.e. the interaction model. Based on the results of the study, it can be concluded that the contribution of surface water tax to regional revenue was as local tax revenue, with a contribution of 87% in 2019, 106% in 2020, and 100.7% in 2021. The obstacle faced in collecting surface water tax is the lack of socialization by the Regional Revenue Agency to taxpayers regarding the rules and sanctions of surface water tax. The solution to the obstacles that occur is by providing periodic socialization, either directly to taxpayers, or through print media and social media